Results of theoretical and experimental studies of the tilt-multistage solar water desalination plant - Juraev Khusniddin; Mirzaev Mirfayz (E3S Web of Conferences, 2023)
This paper presents the results of an experimental study of an inclined-multistage solar water desalination device in the climatic conditions of the Bukhara region. At the same time, changes in temperature in the elements of the device during the season and during the day, as well as changes for water received from the device at this time, are shown in the graphs. Studies carried out in natural conditions showed that the maximum water consumption of 7.5 liters was reached from the surface of 1m2 of the device in July. Based on the generalization of the results of numerous experimental studies, a regression equation was developed that evaluates the effectiveness of the device.